FUTURE GLOBAL NAVIGATION SATELLITE SYSTEMS (GNSS) - Nawzad Kameran Al-Salihi (European Scientific Journal, ESJ, 2015)
Global Positioning System (GPS) has been widely used worldwide for a variety of applications such as air, land and sea. The GPS and the Russian GLONASS are the only fully operational Global Navigation Satellite System (GNSS). Due to its several advantages, such as simplicity of use, successful implementation and global availability, this has been considered as the cornerstone of positioning in navigation system applications for the people who are visually impaired. However, due to standalone single frequency service, the positioning performance has not been sufficient for some accuracy and precision demanding applications. The problems of obtaining high accuracy real time positions in the field have led the navigation community to develop a GNSS augmentation system. However, several questions have been raised with this new development, such as how good the new method is? During any satellite configuration, would it be able to provide the accuracy at the same level? In a reliable way, would it be able to replace conventional GPS method? In this paper, a detailed review of all necessary understandings concerning GNSS and with a focal point on the GPS, GLONASS, Galileo, Beidou and GNSS augmentation systems positioning performance, is provided. The enormous demand to further improve positioning, navigation, and timing capabilities for both civil and military users on existing GNSS systems has directed efforts to modernise the GPS and GLONASS system and introduce new systems such as Galileo navigation system.